Seminar dan Workshop “Membangun Website Pertamamu Menggunakan Gemini AI dan UX Pilot” bagi Karang Taruna Unit 08 Kel. Kebon Sirih - Muhammad Fikri Arrayan; Muhammad Ajar Danu Wiratama; Muhammad Almustofa Khanafi; Muhammad Haidar Althaaf Sutowo; Amar Triadi; Fadli Indra Guci; Rully Mujiastuti; Nurvelly Rosanti; Popy Meilina; Rita Dewi Risanty; Sitti Nurbaya Ambo; Mirza Sutrisno (KENDURI : Jurnal Pengabdian dan Pemberdayaan Masyarakat, 2026)
Digital transformation within local youth organizations faces challenges regarding information technology proficiency and the availability of official publication platforms. This community service initiative aims to accelerate digital literacy within the Karang Taruna Kali Pasir RW 08 youth organization through training in AI-based website development (using Gemini AI and UX Pilot). The implementation method comprises three main stages: preparation (partner needs analysis and material design), execution (seminars, hands-on workshops covering HTML, CSS, and JavaScript, and prompt-engineering guidance), and evaluation and output refinement. Evaluation results indicate a significant improvement in participants' cognitive understanding, evidenced by an increase in the average score from 69 in the pre-test to 97 in the post-test, and a Normalized Gain (N-Gain) index of 0.9125, placing it in the high-effectiveness category. The program's tangible output is the "TarunaHub" web profile, featuring modules for an Overview Dashboard, Event Management, Organizational Gallery, and Organizational Structure. Discussions with the partner organization reveal that the TarunaHub platform and AI proficiency have successfully resolved the lack of digital publication media and empowered the organization's administrators to independently document activities and manage organizational information sustainably.